Antibody to hepatitis C virus in multiply transfused patients with thalassaemia major. Issue 8 (August 1990) - Wonke, B; Hoffbrand, A V; Brown, D; Dusheiko, G
Abstract : Seventeen of 73 (23.3%) multiply transfused patients with thalassaemia major (age range, 1-39 years) tested positive for antibody to hepatitis C virus (anti-HCV). Eleven of the 24 patients regularly transfused in countries outside Britain were anti-HCV seropositive; only six of the 49 regularly transfused in Britain were seropositive. The incidence of anti-HBs and anti-HBc was similar to that of anti-HCV in both the British and foreign patients. The anti-HCV seropositive patients showed significantly higher plasma aspartate aminotransferase activities (AST), mean (SD) 10.2 (70.3) U/l, and serum ferritin concentrations, 4067 (2708) micrograms/l, than the anti-HCV seronegative patients (AST, 33.9 (15.6) U/l; serum ferritin 2051 (2092) U/l), respectively. Among the 36 patients who had earlier undergone liver biopsy 10 of 21 with histological features of chronic active hepatitis or cirrhosis, or both, were seropositive for anti-HCV whereas only one of 15 without histological evidence of chronic viral hepatitis was seropositive for anti-HCV. It is concluded that HCV is a major cause of chronic hepatitis in patients with thalassaemia major and is associated with raised AST activity and serum ferritin concentration compared with patients seronegative for anti-HCV.